2017
DOI: 10.1080/08820139.2017.1288240
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Subsets and Their Functional Activity in Behçet’s Disease

Abstract: Increases in NK1/NK2 ratio and CD16IFN-γ NK1 cells might support the idea of a biased IFN-γ dominant immune response in the mucocutaneous involvement of BD pathogenesis. Although the cytokine secretion pattern was different, no difference was obtained in cytotoxic activity, expression of activatory receptors, or degranulation of NK cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…NK cells have recently been reported to play an important role in Th1 dominance in BD patients, and the Th1-type cytokine IFN-γ is known to inhibit Th17 cells from producing cytokine IL-17 (27). Cosan et al reported an advantage of the NK1 subset, but compared with healthy subjects, the proportions of NK2, NK17, and IL-10-secreting cells in BD patients were lower, and similar cytokine profiles have been observed in BD patients with mucosal skin involvement (28). Because of the inhibitory effect of IFN-γ, the dominant function of NK1 cells was increased, and increased secretion of IFN-γ may inhibit NK2, NK17, and NKreg cells in BD patients.…”
Section: The Role Of Innate Immune Cells In the Pathogenesis Of Behcementioning
confidence: 90%
“…NK cells have recently been reported to play an important role in Th1 dominance in BD patients, and the Th1-type cytokine IFN-γ is known to inhibit Th17 cells from producing cytokine IL-17 (27). Cosan et al reported an advantage of the NK1 subset, but compared with healthy subjects, the proportions of NK2, NK17, and IL-10-secreting cells in BD patients were lower, and similar cytokine profiles have been observed in BD patients with mucosal skin involvement (28). Because of the inhibitory effect of IFN-γ, the dominant function of NK1 cells was increased, and increased secretion of IFN-γ may inhibit NK2, NK17, and NKreg cells in BD patients.…”
Section: The Role Of Innate Immune Cells In the Pathogenesis Of Behcementioning
confidence: 90%
“…In BD patients with mucocutaneous involvement, the cytotoxic activity of the NK cells remained unchanged and there was no significant change in CD107a expression compared to healthy individuals. There was also no significant difference between patients that had frequent oral ulcers and rare oral ulcers ( 125 ). In heterogeneous groups of BD patients, CD107a expression of total NK cells were found to be upregulated when compared to healthy individuals ( 144 , 148 ).…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 91%
“…Current studies demonstrated that these changes in NK cells were probably dependent on the organ involvement. BD patients with arthritis had decreased numbers of NK cells in their blood and synovial fluid compared to healthy controls and AS patients ( 142 ), while there was no such a change in NK cells and their subsets (CD16 bright CD56 dim and CD16 dim CD56 bright cells) in mucocutaneous BD patients during the active phase of the diseases compared to healthy controls and remission phase ( 125 ). Two studies with heterogeneous groups of BD patients demonstrated an increase in the numbers of cytokine secreting NK cells ( 143 , 144 ), while one of them also demonstrated a decline in the numbers of cytotoxic NK cells ( 144 ).…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 96%
See 2 more Smart Citations